2006
DOI: 10.1038/sj.ki.5000343
|View full text |Cite
|
Sign up to set email alerts
|

Early post-transplant urinary IP-10 expression after kidney transplantation is predictive of short- and long-term graft function

Abstract: The early identification of renal transplant recipients at enhanced risk of developing acute and subclinical rejection would allow individualized adjustment of immunosuppression before functional graft injury occurs and would exclude these patients from drug-weaning studies. Protein and reverse transcriptase-polymerase chain reaction-based analyses of candidate markers in urine open the opportunity to closely monitor kidney-transplanted patients non-invasively. The chemokine interferon-inducible protein 10 (IP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
94
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(108 citation statements)
references
References 32 publications
10
94
1
3
Order By: Relevance
“…Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells. Schaub et al 10 first reported the association of CXCL9 and CXCL10, normalized to urine creatinine, with tubulitis.…”
mentioning
confidence: 99%
“…Protein markers have also been assessed for their ability to predict both clinical [3][4][5][6][7] and subclinical TCMR. 4,[8][9][10][11] C-X-C motif chemokine 9 (CXCL9) and CXCL10 are IFNg-dependent, C-X-C motif chemokine receptor 3-binding chemokines that are secreted by infiltrating inflammatory cells and renal tubular and mesangial cells. Schaub et al 10 first reported the association of CXCL9 and CXCL10, normalized to urine creatinine, with tubulitis.…”
mentioning
confidence: 99%
“…Although its utility has not been examined in dialysis patients, higher levels of urinary IP-10 have been associated with greater decline in renal function in patients with diabetic nephropathy (41). Moreover, higher early post-transplant IP-10 concentrations in urine have been associated with worse short-and long-term graft function after renal transplantation (42).…”
Section: Discussionmentioning
confidence: 99%
“…before elevation of serum creatinine) 6. Also, urinary CXCL‐10 mRNA has been shown to be elevated up to 6 to 7 days prior to an acute rejection episode 7. In a recent prospective multicenter study, urinary mRNA of CXCL‐9 (as well as urinary CXCL‐9 protein) was shown to be predictive for the presence of acute rejection 8.…”
Section: Mrnas In Urine As Biomarkers Of Graft Performancementioning
confidence: 99%